Antiproliferative activity of 3,5,7- trihydroxy -6- methoxy flavone obtained from chromolaena leivensis (Hieron) on cancer cell lines of breast, prostate, lung, colon and cervix (2016)
The flavone 3,5,7-trihydroxy-6-methoxyflavone was isolated from leaf extracts of Chromolaena leivensis (Hieron), commonly named plant of cancer. It was identified based on their physicochemical propierties and spectroscopic data. This compound presented a methoxylation at C6, this is uncommon in flavonoids and which may confer some specificity of its biological activity. The cytotoxic activity of this flavonoid was determined on PC3 (prostate), MDA- MB-231 (breast), HT29 (colon), SiHa (cervix) and A549 (lung) cancer cells, using MTT assay, to assess if the flavonoid contributes to the anticancer activity previously proposed for Chromolaena leivensis. The cytotoxic activity of the 3,5,7-trihydroxy-6- methoxy flavone was similar to that obtained for the flavonoid quercetin but was low compared with the positive control vincristine sulphate. The better value of the inhibitory concentration of fifty percent (IC50) 150 µM, was achieved on SiHa cell line, while the lower activity: 4008 µM, was obtained on HT29 cancer cell line. However, severe morphological changes were detected on cytoskeleton and nucleus of the SiHa cells detected by immunofluorescence microscopy analysis of cells exposed to the half of the IC50 concentration obtained for the flavonoid. Data indicate that the flavonoid contributes to the anticancer activity of the extracts of leaves from Chromolaena leivensis, and could broadening the spectrum of flavonoids activity against various types of cancer non hormone-dependent.